2017
DOI: 10.5114/pg.2016.64609
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic versus transhiatal esophagectomy – influence on patient survival

Abstract: AimTo evaluate the survival of patients after surgery of the esophagus/cardia using the transthoracic and transhiatal methods.Material and methodsIn the years 2007–2011, 102 patients were radically treated for cancer of the esophagus/cardia: 24 women and 78 men at the average age of 59.5. There were 38 transthoracic procedures and 64 transhiatal procedures. All patients had a conduit made from the stomach, led through lodges in the esophagus and combined with the stump of the esophagus in the neck following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“… 35 , 36 , 37 , 38 With the transhiatal approach, we obtained a mean proximal resection margin of 42.4 mm, which is similar to margins obtained by other authors with the thoraco-abdominal approach. 32 , 35 , 36 , 37 , 38 Duan reported a 38 mm margin with right thoracoabdominal approach in their patients’ population, which corresponds to the results obtained in our study. 32 Studies have demonstrated that in patients with type S II and S III only in a dismal number of patients the tumor invaded more than 25 mm beyond the proximal margin.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“… 35 , 36 , 37 , 38 With the transhiatal approach, we obtained a mean proximal resection margin of 42.4 mm, which is similar to margins obtained by other authors with the thoraco-abdominal approach. 32 , 35 , 36 , 37 , 38 Duan reported a 38 mm margin with right thoracoabdominal approach in their patients’ population, which corresponds to the results obtained in our study. 32 Studies have demonstrated that in patients with type S II and S III only in a dismal number of patients the tumor invaded more than 25 mm beyond the proximal margin.…”
Section: Discussionsupporting
confidence: 87%
“… 13 , 33 Many studies also confirmed that the overall 5-year survival did not depend on the surgical approach as long as R0 resection could be obtained. 13 , 33 , 35 , 37 , 39 The patients in our cohort had a 5-year OS of 33.4%. The independent predictors for long-term survival were T and N stage, multivisceral resection and microscopic free surgical margins.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…28 A recent study has shown that patients who underwent transthoracic esophagectomy had significantly more lymph nodes removed than those who underwent transhiatal esophagectomy. 16 However, some other studies showed no difference between the two groups. 20,26,29-30 Concordantly, we found no significant difference between the two groups regarding the mean number of dissected lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
“…Most of previous studies found no significant difference between the two groups regarding postoperative deaths and patients’ survival. 15-16,21 However, a meta-analysis in 2014 showed that transhiatal esophagectomy led to lower 30-day postoperative mortality rates. 20…”
Section: Discussionmentioning
confidence: 99%